Contribution of oil palm (Elaeis guineensis J.) plantations to farmers' income in West Sulawesi - Makmur; Nurlaela; Dahniar; Astuti, Niluh Sari; Karim, Ikawati; Abdullah, Muhammad Arafat (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2020)
Oil palm is an industrial plantation that is useful as a producer of cooking oil, industrial oil, and fuel. This research was conducted in West Sulawesi, Indonesia on June to September 2020. The purpose of this study was to determine oil palm, to calculate contribution of non-oil palm and non-farming household and contribution of oil palm plantations to farmers' income. Sampling for respondent in this study was carried by simple random sampling to the oil palm farmers in the study location. This study conducted at one of oil palm location center in Central Mamuju Regency, West Sulawesi by using questionnaires. The first results showed that oil palm is very profitable with an average income of IDR 30,666,620 per hectare per year. The second, source of household income for farmers is obtained from oil palm farming, non-oil palm farming and non-farming activities with an average total household income of the oil palm farmers of IDR 46,363,655 per year. The third, the contribution of oil palm plantations to farmers' income is moderate around 66 percent as a medium category.